Transformation of Human-Technology Relations in Human-Computer Interaction: A Systematic Literature Review - Abdul Manan; Hikmat Kodrat; Apriya Maharani Rustandi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of information technology and computer science has driven a fundamental transformation in education through the use of Learning Management Systems, online and hybrid learning, and artificial intelligence. These changes position technology not merely as a tool but as an actor influencing the learning process and decision-making, while also raising challenges related to the quality of interactions, user experience, and ethical aspects. This study aims to examine the transformation of human-technology relations in digital education through a Human-Computer Interaction (HCI) perspective. The method used is a Systematic Literature Review (SLR) by searching scientific publications in the Google Scholar, Scopus, and ResearchGate databases. Selected articles were analyzed qualitatively through thematic synthesis. The results of the study indicate a paradigm shift in human-computer interaction from a command-based approach to an adaptive, contextual, and user-experience-oriented interaction. Artificial intelligence plays a significant role in enhancing learning personalization, but also has the potential to reduce human control and lead to bias and low system transparency. This study concludes that the development of educational technology needs to integrate the principles of HCI and human-centered design so that digital transformation is not only oriented towards technical efficiency but also maintains autonomy and human values in education.